A model for ensuring data confidentiality: In healthcare and medical emergency - Hameed, Shihab A.; Yuchoh, Habib; Al-Khateeb, Wajdi Fawzi Mohammed (2011)
Data confidentiality is a major problem for healthcare and medical emergency system since it accumulates significant information. Sharing and transmission of private via Internet leads to easily intercept it by unauthorized parties. Attackers need to access private information by capturing data transmission and forging themselves as authorized user. Multilevel security is needed in Healthcare and Medical Emergency since its database contains information of various confidentiality levels. This research, address the confidentiality issue by designing and developing new model for data confidentiality. It provides a view of data sensitivity and suggests areas in cryptography to protect data at different sensitivity levels. The proposed model protects transmitting data using role-base security policy and cryptographic system. We classified related information into several sensitivity levels. A suitable cryptography is provided for each level of data sensitivity to support this System. Result of implementation shows that it keeps specific sensitive data confidential at a certain degree with a good performance comparing with normal system and existing security protocols such as SSL and PGP. Furthermore, the cost of encryption and decryption is not high and kept at acceptable level.